1999
DOI: 10.1038/sj.gt.3300999
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of an optimised gene transfer protocol for human primary T lymphocytes according to clinical requirements

Abstract: Current gene therapeutic protocols directed towards the vectors encoding a truncated human low-affinity nerve treatment of inherited disorders (eg ADA-SCID) and viral growth factor receptor (⌬LNGFR) as a gene transfer infections (eg AIDS), as well as adoptive immunotherapy marker, we obtained transduction frequencies of more than approaches are based on the use of genetically modified 70% of CD3 + cells after two cycles of infection. Our protolymphocytes. Since only insufficient transduction of T cells col is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2000
2000
2004
2004

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 17 publications
2
20
0
Order By: Relevance
“…T-lymphocytes were activated (using anti-CD3 and anti-CD28 antibodies) and cultured in X-Vivo10 containing 8% autologous serum (in the presence of 300 U/ml IL-2) essentially as described. 49 The first transduction was carried with the five vectors SF91, SF91P, SinSF91, SinSF91P and, for control, SF11EGFPrev 24 and with noninfectious supernatant (mock control) in the morning of day 4 using our centrifugation protocol. 49 A second infection cycle was performed in the evening of the same day for the low titer constructs SinSF91 and SinSF91P.…”
Section: Primary Hematopoietic Cells and Lymphocytesmentioning
confidence: 99%
“…T-lymphocytes were activated (using anti-CD3 and anti-CD28 antibodies) and cultured in X-Vivo10 containing 8% autologous serum (in the presence of 300 U/ml IL-2) essentially as described. 49 The first transduction was carried with the five vectors SF91, SF91P, SinSF91, SinSF91P and, for control, SF11EGFPrev 24 and with noninfectious supernatant (mock control) in the morning of day 4 using our centrifugation protocol. 49 A second infection cycle was performed in the evening of the same day for the low titer constructs SinSF91 and SinSF91P.…”
Section: Primary Hematopoietic Cells and Lymphocytesmentioning
confidence: 99%
“…22,23 After titration on human fibroblasts (~2 × 10 6 infectious particles/ml), we infected Jurkat and primary T cells at an MOI of about 1 as described. 24,25 In some experiments, an analogous retroviral vector encoding enhanced green fluorescent protein (eGFP) 23 was used in parallel as a control.…”
mentioning
confidence: 99%
“…[5][6][7][8][30][31][32][33] However, in our systems, excellent gene transfer could be achieved by the simple addition of SeV vector solution without specific reagents or centrifugation. Moreover, optimal SeV-mediated gene transfer to activated T cells could be performed during a relatively brief exposure time (less than 30 min, Figure 4d), with representative results seen in nasal mucosa, 20 in the vasculature, 21 in retinal tissue, 24 as well as in human umbilical cord bloodderived CD34-positive cells.…”
Section: Activated T-cell-directed Gene Transfer Via Sevmentioning
confidence: 99%
“…Although an encouraging human study using a retrovirus demonstrated the success of T-cell-directed gene therapy against severely combined immunodeficiency disease (SCID) owing to adenosine deaminase deficiency (ADA), 1,3 it has been difficult to use this strategy in cases of other diseases, because the gene transfer efficiency is usually a critical factor limiting the outcome. Therefore, current efforts are now focused on the development of pseudotyped vectors 4 and transduction techniques [5][6][7][8] for the use of retroviral vectors for clinical applications.…”
Section: Introductionmentioning
confidence: 99%